Energy Production and Environment - Organisation for Economic Co-operation and Development (Paris: Organisation for Economic Co-operation and Development, 1977)
This study is limited to energy and environment policy up to the year 1985. It is primarily addressed to those who formulate national environmental or energy policies, and a synopsis of four "background papers".
Also published in French under: La production d'énergie et l'environment.
Bibliography: p. 103-107.
ne 25/04/2018
Loan
Keywords: Energy Facilities